2017
DOI: 10.1111/nmo.13062
|View full text |Cite
|
Sign up to set email alerts
|

The BDNF polymorphism Val66Met may be predictive of swallowing improvement post pharyngeal electrical stimulation in dysphagic stroke patients

Abstract: Our findings suggest an association between BDNF and stimulation induced swallowing recovery. Further work will be required to validate these observations and demonstrate clinical utility in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
0
16
2
1
Order By: Relevance
“…In their study, those with the Met allele had shown increased altered response with improvement as assessed by the dysphagia rating scale. They suggested that the negative effects of the Met allele may be switched to protective roles in certain circumstances such as after neurostimulation 44 . This is in sharp contrast to our results that advocate the protective role of the Val allele.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In their study, those with the Met allele had shown increased altered response with improvement as assessed by the dysphagia rating scale. They suggested that the negative effects of the Met allele may be switched to protective roles in certain circumstances such as after neurostimulation 44 . This is in sharp contrast to our results that advocate the protective role of the Val allele.…”
Section: Discussioncontrasting
confidence: 99%
“…They suggested that the negative effects of the Met allele may be switched to protective roles in certain circumstances such as after neurostimulation. 44 This is in sharp contrast to our results that advocate the protective role of the Val allele. These discrepancies may be attributable to the different swallowing outcome parameters employed in the two studies.…”
Section: Ta B L E 1 Baseline Demographics Of Patientscontrasting
confidence: 99%
See 1 more Smart Citation
“…In six studies [26, 30, 33, 55, 89, 103] comprising 1241 cases (585 patients with a GG genotype and 656 without) (Fig. 3) showed patients with AIS who carried at codon 196 of the BDNF , the GA or AA genotypes were more likely to have poor outcome: OR 1.41 (1.02–1.94, p = 0.04).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (7)(8)(9)(10)(11)(12)(13) have reported that genetic polymorphisms may affect the outcomes of stroke. For example, the Val66Met polymorphism in the brain-derived neurotrophic factor (BDNF) gene has been linked to poor motor recovery after stroke (7).…”
Section: Introductionmentioning
confidence: 99%